InterRAI Acute Care Instrument for Seniors in Canadian Hospitals: Findings of an Inter-Rater Reliability Pilot Study. Issue 2 (June 2021) - Boscart, Veronique; Taucar, Linda Sheiban; Heyer, Michelle; Kellendonk, Tabitha; Johnson, Keia; Davey, Meaghan; Peel, Nancye; Heckman, George; Hirdes, John
Background: Older adults are the biggest users of emergency departments and hospitals. However, healthcare professionals are often ill equipped to conduct comprehensive geriatric assessments causing missed opportunities for preventing adverse outcomes. Purpose: To evaluate the inter-rater reliability of the interRAI Acute Care (AC) instrument for hospitalized older adults in two acute care hospitals in Ontario, Canada. Methods: This descriptive study focused on evaluating the interRAI AC instrument, which was designed to facilitate a comprehensive nursing assessment for hospitalized seniors. Sample characteristics were described, and Cohen's Kappa was calculated to derive the inter-rater reliability. Assessment times to complete the instrument were collected as well. Results: The Cohen's Kappa score for the instrument was 0.96. Many older adults who were interviewed had several challenges, including multimorbidity, polypharmacy, and lack of home support. The average time required for nurses to complete the interRAI AC instrument was 22 min. Conclusions: The interRAI AC instrument is reliable for use by trained nurses to conduct a comprehensive assessment. This instrument offers a standardized and efficient approach to assess for care and intervention priorities and could prevent adverse outcomes in hospitalized older adults.